Cyst Fluid From Cystic, Malignant Brain Tumors: A Reservoir of Nutrients, Including Growth Factor-Like Nutrients, for Tumor Cells. Issue 6 (25th January 2017) - Dahlberg, Daniel; Struys, Eduard A.; Jansen, Erwin E.; Mørkrid, Lars; Midttun, Øivind; Hassel, Bjørnar
Abstract: BACKGROUND: Brain tumors may have cysts, whose content of nutrients could influence tumor cell microenvironment and growth. OBJECTIVE: To measure nutrients in cyst fluid from glioblastoma multiforme (GBM) and metastatic brain tumors. METHODS: Quantification of nutrients in cyst fluid from 12 to 18 GBMs and 4 to 10 metastatic brain tumors. RESULTS: GBM cysts contained glucose at 2.2 mmol/L (median value; range <0.8-3.5) and glutamine at 1.04 mmol/L (0.17-4.2). Lactate was 7.1 mmol/L (2.4-12.5) and correlated inversely with glucose level (r = –0.77; P < .001). Amino acids, including glutamate, varied greatly, but median values were similar to previously published serum values. Ammonia was 75 μmol/L (11-241). B vitamins were present at previously published serum values, and riboflavin, nicotinamide, pyridoxal 5΄-phosphate, and cobalamin were higher in cyst fluid than in cerebrospinal fluid. Inorganic phosphate was 1.25 mmol/L (0.34-3.44), which was >3 times higher than in ventricular cerebrospinal fluid: 0.35 mmol/L (0.22-0.66; P < .001). Tricarboxylic acid cycle intermediates were in the low micromolar range, except for citrate, which was 240 μmol/L (140-590). In cystic metastatic malignant melanomas and lung tumors values were similar to those in GBMs. CONCLUSION: Tumor cysts may be a nutrient reservoir for brain tumors, securing tumor energy metabolism and synthesis of cell constituents. Serum is one likely source of cyst fluid nutrients. Nutrient levels in tumor cyst fluid are highly variable, which could differentially stimulate tumor growth. Cyst fluid glutamate, lactate, and phosphate may act as tumor growth factors; these compounds have previously been shown to stimulate tumor growth at concentrations found in tumor cyst fluid.